Management of the Independent Learning Curriculum during the Covid-19 Pandemic - Istaryaningtyas, Istaryaningtyas; L., Silviana; E., Hidayat (LPPM Undiksha, 2021)
The curriculum is something that cannot be avoided in interacting with the educational environment. Covid-19, which has become a pandemic in more than 200 countries in the world, demands changes in various fields, including education, in this case the curriculum. This study aims to examine the status, all things considered, ranging from teachers, learning facilities, students and school partnerships, namely the school committee (parents of students). on the one hand, the readiness of some teachers in mastering technology is still not optimal as a demand for distance learning and the school is not yet optimal in disseminating the curriculum for independent learning or the enactment of the curriculum during the pandemic. This investigation utilizes an illustrative subjective technique which means analyzing and afterward describing the problem obviously, sourced from library research with metaphysical realism as the approach. To help understudies influenced by the pandemic and possibly left behind, instructors are required to complete a symptomatic evaluation. The aftereffects of the appraisal are utilized as the reason for choosing learning procedures and giving healing or extra exercises to understudies who are generally given up. Therefore, we need a humanistic educational approach. The concept of humanistic education aims to make humans have awareness, freedom, and responsibility as individuals but in fact live in society.